Template molecular weight-dependent PEDOT surface energy: impact on the photovoltaic performance of bulk-heterojunctions. Issue 43 (21st October 2022) - Li, Yuda; Xiang, Huaxiang; Wang, Jingyu; Gao, Bowen; Tang, Jingming; Xiao, Cong; Wang, Xunchang; Wang, Feng
Abstract : A simple strategy based on the template M w effect is developed for the realization of high-performance PEDOT AIMs with continuous gradient surface energies, and we found that low surface energy donor (or acceptor) based BHJs favor low surface energy PEDOT. Abstract : Tailoring the template structure is attractive for the realization of high-performance poly(3, 4-ethylenedioxythiophene) (PEDOT) conducting polymers; however, precious little attention has been paid to the molecular weight effect of templates on the surface energy ( γ s ) of PEDOTs. Herein, on the basis of the represent template of polystyrene sulfonic acid, we demonstrate that increasing the template molecular weight is effective to increase the size of PEDOT-rich domains and thus decrease the γ s of PEDOT films, for the first time. After fabrication into organic solar cells with the synthesized PEDOT series as anode interfacial materials (AIMs), we found that PBDB-T:Y6, PM6:Y6, D18-Cl:Y6 and PM6:BTP-ec9 based binary bulk heterojunctions present optimal miscibility and photovoltaic performance (12.96%, 17.21%, 17.30% and 18.19%, respectively) on various AIMs, and the high γ s donor (or acceptor) based bulk heterojunction is partial to AIM with high γ s . Our results not only highlight the important role of template molecular weight in the regulation of PEDOT γ s, but also suggest guidelines to match photoactive bulk heterojunction materials with proper AIMs.